Overcoming deterrent metabolites by gaining essential nutrients: A lichen/snail case study. (August 2019) - Gadea, Alice; Charrier, Maryvonne; Fanuel, Mathieu; Clerc, Philippe; Daugan, Corentin; Sauvager, Aurélie; Rogniaux, Hélène; Boustie, Joël; Le Lamer, Anne-Cécile; Lohézic - Le Devehat, Françoise
Abstract: Specialised metabolites in lichens are generally considered repellent compounds by consumers. Nevertheless, if the only food available is lichens rich in specialised metabolites, lichenophages must implement strategies to overcome the toxicity of these metabolites. Thus, the balance between phagostimulant nutrients and deterrent metabolites could play a key role in feeding preferences. To further understand lichen-gastropod interactions, we studied the feeding behaviour and consumption in Notodiscus hookeri, the land snail native to sub-Antarctic islands. The lichen Usnea taylorii was used because of its simple chemistry, its richness in usnic acid (specialised metabolite) and arabitol (primary metabolite) and its presence in snail habitats. Choice tests in arenas with intact lichens versus acetone-rinsed lichens were carried out to study the influence of specialised metabolites on snail behaviour and feeding preference. Simultaneously, usnic acid and arabitol were quantified and located within the lichen thallus using HPLC-DAD-MS and in situ imaging by mass spectrometry to assess whether their spatial distribution explained preferential snail grazing. No-choice feeding experiments, with the pure metabolites embedded in an artificial diet, defined a gradual gustatory response, from strong repellence (usnic acid) to high appetence (D-arabitol). This case study demonstrates that the nutritional activity of N. hookeri is governed by the chemical quality of the food and primarily by nutrient availability (arabitol), despite the presence of deterrent metabolite (usnic acid). Graphical abstract: The main primary and specialised metabolites in Usnea taylorii are in situ located by mass spectrometry imaging. Arabitol, which is highly palatable to the snail Notodiscus hookeri, counterbalances the deterrent effect of usnic acid and plays a key role in lichen-snail trophic interactions. Image 1 Highlights: The lichen Usnea taylorii contains mainly usnic acid and arabitol. In situ mass spectrometry imaging reveals the spatial mapping of the metabolites. The land snail Notodiscus hookeri consumes lichen parts containing both metabolites. The nutritional activity of snails is governed by the chemical quality of the lichen. Primary metabolites overcome the deterrent effect of specialised metabolites.